TAHAPAN PEKERJAAN STABILITAS LERENG DENGAN RETAINING WALL PADA PROYEK X - Lenita, Helga; Leo, Edison (JMTS: Jurnal Mitra Teknik Sipil, 2025)
Slope stability is a crucial aspect in geotechnical engineering, especially in construction projects involving sloping land. This research addresses the slope stability stage with the application of a retaining wall, a structure that serves to prevent soil displacement and landslides. Slope modeling was performed using PLAXIS 8.6 software. For a slope with a grading of 1H:1.5V, a safety factor of 1.1760 was obtained. To improve stability, the slope was cut to 1H:1V, which gave a safety factor of 1.3720, which is considered safe only for temporary conditions. Furthermore, a temporary drainage system was implemented prior to retaining wall construction using bored piles designed to reach the andesite soil layer. After re-modeling the safety factor increased to 1.5258, indicating a suitable condition for the long term. The process ended with backfilling and implementation of a permanent drainage system. Based on Bowles (1993) and SNI 8460:2017 standards, the minimum safety factor for construction is 1.25 for minimum conditions and 1.3 for temporary conditions, and 1.5 for permanent conditions. The results showed that the application of retaining walls can significantly improve slope stability. ABSTRAK Stabilitas lereng merupakan aspek krusial dalam rekayasa geoteknik, terutama dalam proyek konstruksi yang melibatkan lahan miring. Penelitian ini membahas tahapan stabilitas lereng dengan penggunaan retaining wall, sebuah struktur yang berfungsi untuk mencegah pergeseran tanah dan longsor. Permodelan lereng dilakukan menggunakan perangkat lunak PLAXIS 8.6. Untuk lereng dengan kemiringan 1H:1.5V, menghasilkan faktor keamanan sebesar 1.1760. Untuk meningkatkan stabilitas, dilakukan pemotongan lereng menjadi 1H:1V, yang memberikan faktor keamanan 1.3720, yang dinilai aman hanya untuk kondisi sementara. Selanjutnya, sistem drainase sementara diterapkan sebelum konstruksi retaining wall menggunakan bored pile yang dirancang untuk mencapai lapisan tanah andesit. Setelah dilakukan pemodelan ulang faktor keamanan meningkat menjadi 1.5258, menunjukkan kondisi yang sesuai untuk jangka panjang. Proses diakhiri dengan backfilling dan penerapan sistem drainase permanen. Berdasarkan standar Bowles (1993) dan SNI 8460:2017, faktor keamanan minimum untuk konstruksi adalah 1.25 untuk kondisi minimum dan 1.3 untuk kondisi sementara, serta 1.5 untuk kondisi permanen. Hasil penelitian menunjukkan bahwa penerapan retaining wall dapat meningkatkan stabilitas lereng secara signifikan.